KAJIAN PENGEMBANGAN FASILITAS CHARGING KENDARAAN LISTRIK DI BANDUNG GREATER AREA - Muhammad Hilmi Fauzan, Muhammad Hilmi Fauzan; Wisnu Bayu Pratama, Wisnu Bayu Pratama; Iwan Satriyo Nugroho, Iwan Satriyo Nugroho; Rusdhiyansyah, Rusdhiyansyah (Teknologi Nusantara, 2024)
This research aims to support the acceleration program of battery-based electric motor vehicles in Indonesia, particularly in the Bandung Greater Area, West Java. With the continuous growth of motor vehicles, the development of electric vehicles is crucial to reduce dependence on imported oil and improve air quality. Through the Mixed Method method, this research presents a comprehensive study that covers policy, technology, economic, and environmental aspects related to the development of electric vehicle battery charging infrastructure. It is expected that the results of this research will provide valuable recommendations for the government and society in preparing adequate electric vehicle infrastructure in the future. The research method used involves literature studies, observations, interviews, in-depth analysis, Focus Group Disscusion (FGD) with experts, and questionnaires. This research is also conducted within the framework of supporting the Free Learning Free Campus program, involving students in the research process. It is hoped that the results of this research will contribute significantly to the development of the green economy, improvement of air quality, and the achievement of Sustainable Development Goals (SDGs) related to environmental protection.